Pengaruh Suhu dan Ketebalan Irisan Terhadap Lama Penggorengan dan Karakteristik Keripik Kentang Menggunakan Vacuum Frying - Prasetyo, Gilang Putra; Novita, Dwi Dian; Asmara, Sandi; Warji, Warji (Jurnal Agricultural Biosystem Engineering, 2024)
Potatoes are root crops and are classified as short-lived plants. The growth is bushy and creeping and has a rectangular stem. One effort to maintain the quality and shelf life of fruit is to process it into dry food (fruit chips). The way to produce healthy food without changing its original shape is to use Vacuum Frying technology. The purpose of this study was to produce the best quality potato chips at temperatures of 800C, 850C and 900C and the thickness of the sliced fruit was 1mm, 2mm and 3mm and to find out the temperature and thickness of the sliced fruit needed to produce chips with good quality. best. This study used a factorial complete randomized design using two factors. Each repetition was carried out 3 times, so that 27 experimental units were obtained. The parameters observed in this study were the analysis of material shrinkage, moisture content, frying time and organoleptic tests. The best potato chip frying to use in a vacuum frying machine is at a temperature of 900C and a thickness of 1mm fruit slices with a frying time of 26 minutes.Keywords: potatoes, chips, vacuum frying